Plasma Calcifedol Concentration as a Marker of Vitamin D Deficiency in Newborns with Congenital Malformations - S. А. Fomin; Yu. S. Аleksandrovich; I. А. Kurnikova; K. V. Pshenisnov; А. M. Fomin; I. V. Аleksandrovich (Вестник анестезиологии и реаниматологии, 2021)
Diagnosis of vitamin D deficiency and its management is the most difficult problem of modern neonatology.The objective: to study the concentration of 25(OH)D3 in newborns of St. Petersburg depending on the presence of congenital malformations (CM).Subjects and methods. 60 newborns were examined, their gestational age made 39.4 (38-41) weeks. Children were divided into 2 groups: Group 1 – healthy children, Group 2 – children with CM.Results. Regardless of the presence of CM, the calcifedol plasma concentration was below 15 ng/ml. It was found that children with CM whose plasma calcifedol concentration was below 8.0 ng/ml needed long-term invasive mechanical ventilation (80.0 vs 40.0 hours; p < 0.005) and longer treatment in ICU (7.0 vs 4.0; p < 0,002). Negative correlations were revealed between calcifedol concentration, duration of narcotic analgesics administration (R = -0.44; p = 0.01), duration of mechanical ventilation (R = -0.49; p = 0.003) and stay in ICU (R = -0.54; p = 0.001).Conclusion. The most pronounced deficiency of calcifedol was in children with severe CM requiring long-term treatment in ICU.